PENATALAKSANAAN DISLIPIDEMIA DAN DISPEPSIA PADA LANSIA DENGAN PENGETAHUAN KURANG DAN AKTIVITAS FISIK YANG KURANG MELALUI PENDEKATAN KEDOKTERAN KELUARGA - Rohmah, Zakiah Nur; Mayasari, Diana (Medula, 2024)
Dyslipidemia is a lipid metabolism disorder characterized by an increase or decrease in the levels of lipid fractions in plasma. Dyspepsia is a feeling of discomfort in the upper stomach. In Maret, in 2018 there were 28.8% of the Indonesian population aged ≥ 15 years with abnormal total cholesterol levels. In 2020, the prevalence of dyspepsia was 28 million people, 11.3% of the Indonesian population. The aim of this research is to determine risk factors, clinical problems, and manage patients by applying the principles of family medicine according to evidence-based medicine through a patient centered and family approach. The method of this study is a case report. Primary data through history taking, physical examination and home visits, to complete family data, psychosocial and environmental data. The assessment is carried out based on a holistic diagnosis of the beginning, process and end of the study quantitatively and qualitatively. Result: 69 years old patient with complaints of neck stiffness and headache since two weeks ago. The patient has a history of high cholesterol since the past year and does not regularly take cholesterol medication. The patient likes to eat oily foods and coconut milk. The patient has insufficient nutritional intake. The patient’s total cholesterol level was 271 mg/dL. The patient complained of upper stomach pain, a feeling of bloating in his stomach that had been getting worse for the past 2 days. Complaints were caused by sour, spicy and late eating. The patient experienced this complaint since 30 years ago. The patient was diagnosed with dyslipidemia and dyspepsia. In this case, diagnosis and treatment are carried out in accordance with theories and journals. After the intervention, there was improvement in clinical symptoms, increased knowledge, and changes in the patient’s lifestyle.